Isu dan halangan bagi bekas pesalah untuk bekerja: satu perspektif - Nur Diyanah Hidayat; Siti Marziah Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ex-offenders are facing major challenges after their release to survive in the community. Among the challenges are stigma from the community, physical and mental health issues, financial problem because of unemployment and loss of significant others. They need to be guided to manage issues regarding employment, family, interpersonal relationship, and self-management. This article will discuss issues and barriers for ex-offenders to return to work or join the workforce. Past findings showed that ex-convicts and ex-drug addicts are still facing with barriers which withhold them from joining the job market. They frequently become the victims of rejection, bias, being bullied, and being segregated by co-workers. Barriers in employment may also be rooted from themselves, such as attitude problem, bad work culture, aggressive personality, and disciplinary issue. Thus, effective programmes and interventions need to be implemented for ex-offenders to increase their employability, and hence joining the community.